2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594511
|View full text |Cite
|
Sign up to set email alerts
|

People as Sensors: Imputing Maps from Human Actions

Abstract: Despite growing attention in autonomy, there are still many open problems, including how autonomous vehicles will interact and communicate with other agents, such as human drivers and pedestrians. Unlike most approaches that focus on pedestrian detection and planning for collision avoidance, this paper considers modeling the interaction between human drivers and pedestrians and how it might influence map estimation, as a proxy for detection. We take a mapping inspired approach and incorporate people as sensors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…These problems are orthogonal to the problem of occluded factor inference from the behaviour of an observed vehicle. The works most closely related to ours are the works of Sun et al [29] and Afolabi et al [1] who infer occluded obstacles from the actions of observed vehicles. Sun et al [29] infer so-called social information (i.e., occluded factors) with an inverse-planning approach based on a reward function learned with inverse reinforcement learning.…”
Section: Related Workmentioning
confidence: 79%
“…These problems are orthogonal to the problem of occluded factor inference from the behaviour of an observed vehicle. The works most closely related to ours are the works of Sun et al [29] and Afolabi et al [1] who infer occluded obstacles from the actions of observed vehicles. Sun et al [29] infer so-called social information (i.e., occluded factors) with an inverse-planning approach based on a reward function learned with inverse reinforcement learning.…”
Section: Related Workmentioning
confidence: 79%
“…Similarly, several studies have attempted to predict the states of objects in blind spots in traffic scenes. Afolabi et al [15] estimated occupancy grids of pedestrians in blind spots based on visible driver behaviors. Sun et al [16] proposed a planning framework for driving behaviors using human traffic participants as distributed sensors.…”
Section: B Prediction Of Invisible Objectsmentioning
confidence: 99%
“…Because all vehicles cannot be equipped with vehicle to vehicle (V2V) communications at present, autonomous vehicles should perceive the surrounding environment based on local sensors. Social perception has been devised to deal with local sensor limits [33], [34]. The perceived vehicle information could be used to infer the area beyond the blind spot or sensor limit.…”
Section: Introductionmentioning
confidence: 99%